Seasonal variation of birch and grass pollen loads and allergen release at two sites in the German Alps - Jochner, Susanne; Lüpke, Marvin; Laube, Julia; Weichenmeier, Ingrid; Pusch, Gudrun; Traidl-Hoffmann, Claudia; Schmidt-Weber, Carsten; Buters, Jeroen T.M.; Menzel, Annette (Atmospheric environment (1994), 2015)
Less vegetated mountainous areas may provide better conditions for allergy sufferers. However, atmospheric transport can result in medically relevant pollen loads in such regions. The majority of investigations has focused on the pollen load, expressed as daily averages of pollen per cubic meter of air (pollen grains/m³); however, the severity of allergic symptoms is also determined by the actual allergen content of this pollen, its pollen potency, which may differ between high and low altitudes. We analysed airborne birch and grass pollen concentrations along with allergen content (birch: Bet v 1, grass: Phl p 5) at two different altitudes (734 and 2650 m a.s.l.) in the Zugspitze region (2009–2010). Back-trajectories were calculated for the high altitude site and for specific days with abrupt increases in pollen potency. We observed several days with medically relevant pollen concentrations at the highest site. In addition, a few days with pollen were not associated with allergens and vice versa. The calculated seasonal mean allergen release per pollen grain was 1.8–3.3 pg Bet v 1 and 5.7 pg Phl p 5 in the valley and 1.1–3.7 pg Bet v 1 and 0.7–1.5 pg Phl p 5 at the high altitude site. Back-trajectories revealed that high pollen potency at the higher site was generally associated with south-westerly to south-easterly (birch), or northerly (grass) wind directions. By investigating days with sudden increases in pollen potency, however, it was difficult to draw definitive conclusions on long- or short-range transport. Our findings suggest that people allergic to pollen might suffer less at higher altitudes and further indicate that a risk assessment relying on the actual concentration of airborne pollen does not necessarily reflect the actual allergy exposure of individuals. •Pollen/allergen concentrations were comparably low at a high altitude station.•However, we also identified some days with relevant pollen/allergen concentrations.•Some days with sampled pollen were related to no allergen content and vice versa.•A risk assessment solely based on pollen concentrations is not inclusive.•More attention should be paid to the actual allergen content of pollen.